A Study for Producing 3D Model Space from 2D Digital Picture using Photogrammetry Technology - Kitagawa, Etsuji; Noda, Hajime; Tanaka, Shigenori; Furuta, Hitoshi; Muraki, Hirokazu (journal of Civil Engineering Information Processing System, 2000)
With the advance of computer technologies, 3D CAD and CG have been noticed in recent years.This tendency has also led to the increase of interest toward a photogrammetry technique, which is used to acquire 3D data from two pieces of 2D digital picture. By using this technique, the measuring of an object from a distance, which had been difficult, can now be easily done. In present study, we have established a new technology by using an automatic decision method which can obtain the optimal passpoint. This technique offers everybody to obtain 3D data easily.